The experiences of transgender female sex workers within their families, occupation and the health care system - Vickerman, Shelley Ann (University of the Western Cape, 2019)
Magister Artium (Psychology) - MA(Psych) === There is a dearth of scholarly literature surrounding transgender female sex workers (TFSW) within South Africa. Their voices are often marginalised and not adequately heard in the literature and in a society that generally views gender as a fundamental element of the self, determining their subject positions against binaried heteronormative gender ideals. This process of the ‘othering’ of TFSW, is exacerbated by the moralistic judging of their occupation of sex work. This has left many TFSWs vulnerable to emotional abuse such as being socially stigmatised, discriminated against and socially isolated. The literature further echoes vulnerability to physical violence, such as hate crimes, rape, heightened HIV infection, homelessness, police brutality and murder. The current study aimed to explore the subjective experiences of TFSW within their families, occupations and the healthcare system within the Cape Town metropole, South Africa. The study was framed within an intersectional feminist epistemological position, highlighting intersecting identities that marginalise groups of people. Informant driven sampling was used in the case of this study where a total of eleven participants were individually interviewed using a semi-structed approach – interviews ranged from 35-90 minutes. The data collected was subsequently analysed using thematic analysis and the three themes that emerged were: transgender female (TGF), Sex work and HIV. Family rejection and abuse based on participants non-conforming gender identity was expressed by participants. Repressive home circumstances led to many opting to live on the street. Participants described being introduced to sex work through a network of other homeless TFSW, also described as ‘Sisters’ (who fulfil the role of family) as a means of survival. Sex work for TGFs is a particularly dangerous job, as sex workers run the risk of being exposed as TGFs, often resulting in severe physical harm for some. To cope with their severe realities of violence and homelessness, many reported turning to substances, such as alcohol and methamphetamine. A total of ten participants described being HIV positive and adherence was very poor among the group. This could be attributed to stigmatisation from health workers, substance use and homelessness. This group of women, though vulnerable and structurally oppressed, displayed exceptional resilience. It is suggested that further research should be conducted on this group in the South African context for a clearer understanding of their needs and improved policy, as well as interventions for TFSW.